Modulation of the IGF1R-MTOR pathway attenuates motor neuron toxicity of human ALS SOD1G93A astrocytes. Issue 12 (2nd December 2021) - Granatiero, Veronica; Sayles, Nicole M.; Savino, Angela M.; Konrad, Csaba; Kharas, Michael G.; Kawamata, Hibiki; Manfredi, Giovanni
ABSTRACT: ALS (amyotrophic lateral sclerosis), the most common motor neuron disease, causes muscle denervation and rapidly fatal paralysis. While motor neurons are the most affected cells in ALS, studies on the pathophysiology of the disease have highlighted the importance of non-cell autonomous mechanisms, which implicate astrocytes and other glial cells. In ALS, subsets of reactive astrocytes lose their physiological functions and become toxic for motor neurons, thereby contributing to disease pathogenesis. Evidence of astrocyte contribution to disease pathogenesis are well established in cellular and animal models of familial ALS linked to mutant SOD1, where astrocytes promote motor neuron cell death. The mechanism underlying astrocytes reactivity in conditions of CNS injury have been shown to involve the MTOR pathway. However, the role of this conserved metabolic signaling pathway, and the potential therapeutic effects of its modulation, have not been investigated in ALS astrocytes. Here, we show elevated activation of the MTOR pathway in human-derived astrocytes harboring mutant SOD1, which results in inhibition of macroautophagy/autophagy, increased cell proliferation, and enhanced astrocyte reactivity. We demonstrate that MTOR pathway activation in mutant SOD1 astrocytes is due to post-transcriptional upregulation of the IGF1R (insulin like growth factor 1 receptor), an upstream positive modulator of the MTOR pathway. Importantly, inhibition of the IGF1R-MTOR pathway decreases cell proliferation and reactivity of mutant SOD1 astrocytes, and attenuates their toxicity to motor neurons. These results suggest that modulation of astrocytic IGF1R-MTOR pathway could be a viable therapeutic strategy in SOD1 ALS and potentially other neurological diseases. Abbreviations: ACM: astrocyte conditioned medium; AKT: AKT serine/threonine kinase; ALS: amyotrophic lateral sclerosis; BrdU: thymidine analog 5-bromo-2'-deoxyuridine; CNS: central nervous system; EIF4EBP1/4EBP1: eukaryotic translation initiation factor 4E binding protein 1; GFAP: glial fibrillary acidic protein; IGF1R: insulin like growth factor 1 receptor; INSR: insulin receptor; iPSA: iPSC-derived astrocytes; MAP1LC3B/LC3B: microtubule associated protein 1 light chain 3 beta;MTOR: mechanistic target of rapamycin kinase; NES: nestin; PPK1: 3-phosphoinositide dependent protein kinase 1; PI: propidium iodide; PPP: picropodophyllotoxin; PTEN: phosphatase and tensin homolog; S100B/S100β: S100 calcium binding protein B; SLC1A3/ EAAT1: solute carrier family 1 member 3; SMI-32: antibody to nonphosphorylated NEFH; SOD1: superoxide dismutase 1; TUBB3: tubulin beta 3 class III; ULK1: unc-51 like autophagy activating kinase 1.